Аналіз різновидів філаменту для 3d друку - Долгошея, І. Д. (ХНУРЕ, 2024)
In theses, varieties of filaments for 3d printing are considered. In order to identify the advantages and disadvantages, the justification of the need to create an automated thermosaver for saving filament for 3D printing is carried out.
Keywords: філамент; 3D друк